Strategi Pengembangan Open Access Institutional Repository - Faizuddin Harliansyah (Pusat Publikasi Ilmiah UIN Fatmawati Sukarno Bengkulu, 2017)
In order to formulate the vision, mission and objectives of repository development, the university's repository development team should comprehensively comprehend, among others: [1] the sense of institutional repository; [2] types of repositories other than institutional repository and their respective characteristics; [3] the relationship between scholarly communication, open access, and the idea of institutional repository development. The development of a repository is a new challenge and a very important role for college libraries. This role has been largely done by university libraries in developed countries. To embody this new role, the college library must provide some knowledge and technical skills related.